Protein Denaturation in Foam. - Clarkson, JR; Cui, Z; Darton, R (1999)
As part of a study of protein denaturation in foam we have measured the surface tension and the changes in protein structure occurring at the interface for lysozyme, pepsin, BSA, YADH, IgG, and catalase. The apparent CMC values were found to be dependent on the size and rigidity of the molecule. The variability of protein damage at a gas-liquid interface in foam was assessed using these proteins. The foams were produced under controlled conditions in a bubble column and were found to induce conformational changes in the protein molecules, but no fragmentation or disassociation of subunits occurred. Tertiary structural changes were detected in all the proteins studied, with some proteins forming aggregates. For pepsin, the secondary structure was also found to be altered. Enzyme solutions were used to determine the degree of biological activity retained after foaming for proteins with different structural characteristics. The more rigid proteins were found to display a low surface activity and a low degree of damage in foam. Pepsin suffered the highest rate of damage, which is thought to be a result of its inability to refold following denaturation. Copyright 1999 Academic Press.